Hematological Study on Obligate Air Breathing, Fish Channa punctatus (Bloch) Exposed to Cythion: Hematological Study on Obligate Air Breathing, Fish Channa punctatus (Bloch) Exposed to Cythion - Kumari, Rina (International Journal of Pharmaceutical & Biological Archive, 2018)
An attempt has been taken to analyze the effect of cythion on the hematological parameters of an air-breathing fish Channa punctatus. It is found that this pesticide causes a significant reduction in red blood cell count, hemoglobin content, oxygen capacity, and packed cell volume.